Investigation of respiratory muscle strength and its influence on exercise capacity and quality of life in patients with idiopathic pulmonary fibrosis: IPF and Respiratory Muscle Strength - Pehlivan, Esra; Zeren, Melih; Niksarlıoğlu, Elif Yelda; Karaahmetoğlu, Fulya Senem; Özcan, Zeynep Betül; Balcı, Arif; Demirkol, Barış; Çetinkaya, Erdoğan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background: Adequate respiratory muscle strength is required to meet the increased ventilatory demand during physical activities. However, it is not well known whether respiratory muscle strength is impaired in patients with idiopathic pulmonary fibrosis (IPF). Objectives: This study aimed to investigate the relationship between respiratory muscle strength and exercise capacity, quality of life, physical activity level, and fatigue in IPF patients. Methods: The study comprised 30 individuals with idiopathic pulmonary fibrosis (IPF) and 30 healthy controls. Maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) were measured to assess respiratory muscle strength. The International Physical Activity Questionnaire-Short Form, 6-minute walk test distance (6MWD), St George Respiratory Questionnaire (SGRQ), and Fatigue Severity Scale (FSS) were employed to evaluate physical activity level, exercise capacity, quality of life, and fatigue severity, respectively. Results: MIP (81±29 vs.73±20 cmH2O) and MEP (93±31 vs. 93±34 cmH2O) did not differ significantly between IPF patients and controls (p>0.05). In patients with IPF, MIP was significantly correlated with 6MWD (r=0.533), SGRQ (r=-0.428), and FSS (r=-0.433). Multivariate models including MIP, MEP, FEV1, FVC, and PA level explained 74% of the variance in the 6MWD (p<0.001), and MIP, FEV1, and PA level were independent predictors of the 6MWD, with FEV1 being the strongest predictor (β=0.659). Multivariate models predicting SGRQ revealed none of MIP, FEV1 or PA level was directly influencing the SGRQ score. Conclusions: This study suggests that patients with IPF do not have respiratory muscle weakness. Inspiratory muscle strength has a direct influence on exercise capacity but an indirect effect on quality of life, probably by influencing exercise capacity.